DAMPAK KEBIJAKAN GREEN FINANCE TERHADAP SEKTOR KEUANGAN GLOBAL : LITERATURE REVIEW - Tazida Berliana Elma El Hakim; Mirzam Arqy Ahmadi (Cahaya Ilmu Bangsa, 2024)
Green finance policy is one of the key steps in supporting sustainable development and climate change mitigation. Through instruments such as green bonds and green loans, green finance has successfully redirected capital flows to environmentally friendly and low-carbon initiatives. This study attempts to analyse the effect of green finance policies on the global financial sector using a literature review technique. The findings of this study show that this strategy not only encourages green finance innovation, but also enhances financial sector stability in the face of climate change challenges. However, there are still some obstacles in implementing this policy, including regulatory gaps between countries, limited access to funds for developing countries, and potential greenwashing. This study shows that to maximise the benefits of green finance, the global regulatory framework should be strengthened, transparency improved, and developing countries receive more support.